Handbook of Cultural Developmental Science - Bornstein (Psychology Press, 2012)
Researchers and theoreticians commonly acknowledge the profound impact of culture on all aspects of development. However, many in the field are often unaware of the latest cultural literatures or how development proceeds in places other than their home locations.